A novel Medical Achievement Self-efficacy Scale (MASS): A valid and reliable tool. (July 2013) - Turan, Sevgi; Valcke, Martin; De Maeseneer, Jan; Aper, Leen; Koole, Sebastiaan; De Wispelaere, Christine; Deketelaere, Ann; Derese, Anselme
<x xml:space="preserve">Abstract</x> In search for an instrument to measure overall curriculum impact, we developed a Medical Achievement Self-efficacy Scale (MASS) and presented it to medical students enrolled in the different years of the integrated Ghent curriculum. The research aim was to study the validity and reliability of this new scale. MASS items were constructed based on the end terms of the Ghent curriculum, as it is related to the general competency frameworks of CanMEDs and the Five-star Doctor. The scale includes at least two items for each CanMEDS competency domain. Items were examined by seven experts in view of content and face validity. This resulted in an MASS version, containing 18 items, to be rated on a five-point Likert scale. This version was piloted on 94 undergraduate medical students enrolled at the Catholic University of Leuven. The final version was presented to 1066 undergraduate medical students enrolled at Ghent University. Reliability of the MASS scale was high (α = 0.89). As expected, self-efficacy scores increased significantly over the years (F = 39.11, p < 0.001). In view of determining predictive validity, regression analysis was carried out to predict students' academic achievement from self-efficacy scores. As expected, MASS scores significantly predicted Maastricht Progress Test scores (F = 108.18, p < 0.001).